Indigenous voice in tackling violent extremism in Kenya: coloniality and exclusion of African women - Oando, Samwel (Methodologies in critical terrorism studies, 2024)
This chapter problematises the missing voices of Indigenous [African] knowledge systems, and African women within strategies for Countering Violent Extremism (CVE). An increasing number of donor-funded CVE programmes on the African continent are framed as speaking particularly to “African” contexts. However, such initiatives are underpinned by Eurocentric knowledge systems that are significantly different to the local practice. The dominance by “white male voices” within critical academic spaces also freezes theoretical spaces for subaltern communities of practice. By analysing interviews with local CVE practitioners in Kenya, this chapter demonstrates how knowledge production by African women on CVE initiatives is rendered “informal” both within academic and policy spaces. In essence, Indigenous knowledge and methodologies for CVE are either systematically excluded or local voices subjugated. The participation of local actors within CVE developments is therefore constrained, meaning that local concerns are seldom considered by the interventions to the detriment of sustainability. This exclusion subverts further the voices of Kenyan women who are already restricted by local patriarchal systems. Interventions for CVE designed exclusively on Western knowledge and assumptions of knowledge transferability, therefore, present a double threat of systemic and gender exclusion.